A nonlinear Granger causality test between stock returns and investor sentiment for Chinese stock market: a wavelet-based approach. Issue 21 (2nd May 2016) - Chu, Xiaojun; Wu, Chongfeng; Qiu, Jianying
ABSTRACT: In this article, we re-examine the causality between the stock returns and investor sentiment in China. The number of net added accounts is used as a proxy for investor sentiment. To mimic the different investment horizons of market participants, we use the wavelet method to decompose stock returns and investor sentiment into time series with different frequencies. Additionally, we test for nonlinear causal relationships based on Taylor series approximation. Our results indicate that there is a one-directional linear causality from stock returns to investor sentiment on the original series, while there is a strong bi-directional nonlinear causality between stock returns and investor sentiment at different timescales.